(untitled) (Revista Argentina de Cirugía, 2025)
Median arcuate ligament syndrome (MALS), also known as Dunbar syndrome or celiac axis compression syndrome (CACS), is a significant topic because it is a rare condition that is diagnosed by exclusion after other, more common conditions, such as gastritis or biliary colic, have been ruled out. It is caused by compression of the celiac trunk due to low insertion of the diaphragm. This syndrome is characterized by the clinical triad of postprandial abdominal pain, weight loss, and nausea or vomiting. The traditional treatment for MAL involves surgically dividing the ligament fibers. We present a case of a 34-year-old female patient with CACS, which was resolved through laparoscopic surgery using the da Vinci surgical system. The role of minimally invasive surgery as a treatment for this syndrome is a safe alternative to open surgery